2022
DOI: 10.1039/d2nh00023g
|View full text |Cite
|
Sign up to set email alerts
|

Etched-spiky Au@Ag plasmonic-superstructure monolayer films for triple amplification of surface-enhanced Raman scattering signals

Abstract: The triple signal amplification for the SERS detection based on 2D monolayer film of etched spiky Au@Ag NPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…99 The self-assembly of nanoparticles on a flexible planar substrate has been reported in many studies. 101,102 Huang's group has reported a new fabrication method based on tailoring the contact angle of nanoparticles to assemble the nanoparticles instantly (within 5 s) on silicon wafer. 103 In another study, the same group has reported controlling the SERS intensity of a planar system (containing a monolayer of gold nanoparticles) by adjusting the shrinkage of the substrate through light.…”
Section: Nanomaterials For Sersmentioning
confidence: 99%
“…99 The self-assembly of nanoparticles on a flexible planar substrate has been reported in many studies. 101,102 Huang's group has reported a new fabrication method based on tailoring the contact angle of nanoparticles to assemble the nanoparticles instantly (within 5 s) on silicon wafer. 103 In another study, the same group has reported controlling the SERS intensity of a planar system (containing a monolayer of gold nanoparticles) by adjusting the shrinkage of the substrate through light.…”
Section: Nanomaterials For Sersmentioning
confidence: 99%
“…Plasmons arising on the surface of metallic nanostructures have allowed manipulation and enhancement of the typical molecular vibrations characteristic of the molecules adsorbed to their surfaces that are to be analyzed. Various groups have explored this plasmonic property and exploited its uses toward the molecular detection of analytes through the phenomenon termed surface-enhanced Raman scattering (SERS), especially through the use of heterometallic nanoparticles, with many of the nanoparticles proving to be much-needed additions to medical imaging and general molecular detection methods. However, this plasmonic resonance has only been shown to arise in nonferromagnetic metals as well as more reactive alkali and alkaline-earth metal nanostructures. This is due to Fe and Co’s real component of permittivity being positive, meaning they have weak interaction with incident light that do not allow the generation of surface plasmons, thereby dampening any possible surface plasmon resonance polaritons (SPP) at their metal/dielectric interface. Specifically, a new method of detection has arisen from the hybridized resonance pattern that occurs because of alloying FeCo with a noble metal to create ferroplasmonic nanostructures. , Lopez-Ortega et al have reported the magneto-optical enhancement in metallic Ag/FeCo core/shell nanoparticles with 50 emu/g magnetization .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, surface-enhanced Raman scattering (SERS) analysis is simple to operate, takes less time to detect, and does not require complex pre-treatment of samples, so it can greatly improve the detection efficiency and shows potential application for SEC detection. Noble metal nanomaterials have been widely applied in SERS research because of their strong localized surface plasmon resonance (LSPR). , LSPR can cause localized electromagnetic (EM) field enhancement, and the EM field enhancement effect is one of the two widely accepted theoretical mechanisms for SERS enhancement . Most SERS sensors rely on the Raman signal of the target itself for quantitative detection or require additional modification of the Raman reporter on the plasmonic nanoprobes to obtain the strong detection signal. These will lead to the following limitations: (1) The targets without an inherent Raman signal or with low Raman intensity cannot be sensitively detected. (2) The additional modification of Raman reporters may induce unstable SERS signals and are susceptible to the surrounding complex sample matrices.…”
Section: Introductionmentioning
confidence: 99%